Necrotizing ulcerative stomatitis as initial presentation of undiagnosed HIV infection: A case report and review of literature. Issue 6 (November 2017) - Peters, Scott M.; Heinz, Matthew J.; Koslovsky, David A.; Yoon, Angela J.; Philipone, Elizabeth M.
Abstract: There are a multitude of oral manifestations of human immunodeficiency virus (HIV), many of which have decreased in frequency following the introduction of combination antiretroviral therapy (cART) in 1996. Atypical periodontal disease is an example of an oral manifestation that is infrequently seen yet strongly associated with HIV infection. HIV-associated periodontal disease can be classified into three categories, linear gingival erythema, necrotizing ulcerative gingivitis (NUG), and necrotizing ulcerative periodontitis (NUP), which vary based on disease severity. When this disease process extends beyond the alveolar ridges and causes massive tissue destruction, it is termed necrotizing ulcerative stomatitis (NUS). Herein, we report a case of a 20-year-old male patient with undiagnosed HIV in whom necrotizing ulcerative stomatitis was the first presenting sign of underlying disease.